Penerapan Model Pembelajaran Filpped Classroom dapat Meningkatkan Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Tanah Jawa Tahun Pembelajaran 2023/2024 - Irma Farida Batu Bara; Ratna Saragih; Rida Gultom; Betty A.S Pakpahan; Wilson Simanjuntak (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The purpose of this study is to determine the learning motivation of Christian Religious Education and Ethics of students who are taught using the Flipped Classroom Learning Model is higher than students who are taught using the Conventional Learning Model in Grade XI Students of SMA Negeri 1 Tanah Java for the 2023/2024 Academic Year. This study uses a Posttest-Only Control type experimental method. The population is all XI SMA Negeri 1 Tanah Java for the 2023/2024 Academic Year which totals 171 people. The sample was determined by a technique taken deliberately (purposive sampling) with the conditions set by the learning material that was experimented on in the class, namely 31 students in class XI MIA 3 as the experimental class and class XI MIA totaling 30 people as the control class. The research instrument used a questionnaire of 29 items. The t-test used was the Separated Variance t-test according to the analysis requirements test of n1≠n2 and the variance of the two sample groups was non-homogeneous variance (Ơ₁² ≠ Ơ₂²). The results of the hypothesis test obtained a tcal value = 10.987>ttable 5.093, then H0 was rejected and Ha was accepted. This study concluded that the motivation to learn Christian Religious Education and Ethics of students who were taught using the Flipped Classroom Learning Model was higher than that of students who were taught using the Conventional Learning Model in Grade XI Students of SMA Negeri 1 Tanah Java for the 2023/2024.